2020
DOI: 10.7554/elife.55246
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin signaling by maternal neurons upon stress ensures progeny survival

Abstract: 19Germ cells are vulnerable to stress. Therefore, how organisms protect their future progeny from 20 damage in a fluctuating environment is a fundamental question in biology. We show that in 21Caenorhabditis elegans, serotonin released by maternal neurons during stress ensures the 22 viability and stress resilience of future offspring. Serotonin acts through a signal transduction 23 pathway conserved between C. elegans and mammalian cells to enable the transcription factor 24 HSF1 to alter chromatin in soon-to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 116 publications
(8 reference statements)
4
39
0
Order By: Relevance
“…Interestingly, pathogenic bacteria are not the only environmental conditions that impact the worm for multiple generations. It has been shown that parental experiences, including dietary restriction, osmotic stress, temperature changes, olfactory imprinting, and prolonged starvation, can regulate the physiology of the offspring, some of which last for several generations and are mediated by small RNA pathways (Burton et al, 2017;Das et al, 2020;Demoinet, Li, & Roy, 2017;Greer et al, 2011;Hibshman, Hung, & Baugh, 2016;Jobson et al, 2015;Klosin, Casas, Hidalgo-Carcedo, Vavouri, & Lehner, 2017;Ni et al, 2016;Palominos et al, 2017;Posner et al, 2019;Rechavi et al, 2014;Remy, 2010;Schott, Yanai, & Hunter, 2014). These studies together show that C. elegans has evolved diverse adaptive strategies to generate long-term plasticity that lasts for multiple generations.…”
Section: Intergenerational Effectsmentioning
confidence: 99%
“…Interestingly, pathogenic bacteria are not the only environmental conditions that impact the worm for multiple generations. It has been shown that parental experiences, including dietary restriction, osmotic stress, temperature changes, olfactory imprinting, and prolonged starvation, can regulate the physiology of the offspring, some of which last for several generations and are mediated by small RNA pathways (Burton et al, 2017;Das et al, 2020;Demoinet, Li, & Roy, 2017;Greer et al, 2011;Hibshman, Hung, & Baugh, 2016;Jobson et al, 2015;Klosin, Casas, Hidalgo-Carcedo, Vavouri, & Lehner, 2017;Ni et al, 2016;Palominos et al, 2017;Posner et al, 2019;Rechavi et al, 2014;Remy, 2010;Schott, Yanai, & Hunter, 2014). These studies together show that C. elegans has evolved diverse adaptive strategies to generate long-term plasticity that lasts for multiple generations.…”
Section: Intergenerational Effectsmentioning
confidence: 99%
“…Finally, she discussed her recent findings that serotonin acts through a signal transduction pathway conserved between C. elegans and mammalian cells to enable the transcription factor HSF1 to alter chromatin in soon-to-be fertilized germ cells by recruiting the histone chaperone FACT, displacing histones, and initiating protective gene expression. Without serotonin release by maternal neurons, FACT is not recruited by HSF1 in germ cells and progeny of stressed C. elegans mothers fail to complete development (Das et al 2020). These studies are just beginning to uncover how stress sensing by maternal neurons, coupled to HSF1-dependent transcription in the germline, could result in the epigenetic remodeling of offspring (Das et al 2020).…”
Section: Organismal and Intercellular Level Stress Responsesmentioning
confidence: 99%
“…Without serotonin release by maternal neurons, FACT is not recruited by HSF1 in germ cells and progeny of stressed C. elegans mothers fail to complete development (Das et al 2020). These studies are just beginning to uncover how stress sensing by maternal neurons, coupled to HSF1-dependent transcription in the germline, could result in the epigenetic remodeling of offspring (Das et al 2020).…”
Section: Organismal and Intercellular Level Stress Responsesmentioning
confidence: 99%
“…We then allowed these oocytes to complete maturation, undergo fertilization, and develop into adults at normal growth temperature of 20°C. To activate HSF-1 in the germline, we chose regimen of long heat exposure (30 minutes or 60 minutes to 34°C) that is typically used to activate HSF-1 throughout the animal (33)(34)(35)(36) and a shorter, 5-minute heat-shock at 34°C, which we have previously shown is sufficient to induce HSF-1 transcriptional activity (33).…”
mentioning
confidence: 99%
“…These animals express a truncated HSF-1 protein lacking the transactivation domain, where HSF-1 binds constitutively to the promoter regions of its target genes in the absence of heat shock, but is deficient in heat-shock induced binding ( Fig. S3 C, D) and transcription (33). Progeny that developed from heat-shocked germ cell oocytes of hsf-1 (sy441) I animals also did not undergo early life programming and did not display enhanced stress resilience (Fig.…”
mentioning
confidence: 99%